Proteomic analysis response of rice (Oryza sativa) leaves to ultraviolet-B radiation stress - Sah, Saroj Kumar; Jumaa, Salah; Li, Jiaxu; Reddy, K. Raja (Frontiers in Plant Science, 2022)
Rice (Oryza sativa) is a human staple food and serves as a model organism for genetic and molecular studies. Few studies have been conducted to determine the effects of ultraviolet-B (UV-B) stress on rice. UV-B stress triggers morphological and physiological changes in plants. However, the underlying mechanisms governing these integrated responses are unknown. In this study, we conducted a proteomic response of rice leaves to UV-B stress using two-dimensional gel electrophoresis and identified the selected proteins by mass spectrometry analysis. Four levels of daily biologically effective UV-B radiation intensities were imposed to determine changes in protein accumulation in response to UV-B stress: 0 (control), 5, 10, and 15 kJ m−2 d−1in two cultivars, i.e., IR6 and REX. To mimic the natural environment, we conducted this experiment in Sunlit Soil-Plant-Atmosphere-Research (SPAR) chambers. Among the identified proteins, 11% of differentially expressed proteins were found in both cultivars. In the Rex cultivar, only 45% of proteins are differentially expressed, while only 27.5% were expressed in IR6. The results indicate that REX is more affected by UV-B stress than IR6 cultivars. The identified protein TSJT1 (spot 16) in both cultivars plays a crucial role in plant growth and development during stress treatment. Additionally, we found that UV-B stress altered many antioxidant enzymes associated with redox homeostasis and cell defense response. Another enzyme, the glyceraldehyde-3-phosphate dehydrogenase (GAPDH), has been identified as spot 15, which plays an essential role in glycolysis and cellular energy production. Another vital protein identified is glycosyl hydrolase (GH) as spot 9, which catalyzes the hydrolysis of glycosidic bonds in cell wall polymers and significantly affects cell wall architecture. Some identified proteins are related to photosynthesis, protein biosynthesis, signal transduction, and stress response. The findings of our study provide new insights into understanding how rice plants are tailored to UV-B stress via modulating the expression of UV-B responsive proteins, which will help develop superior rice breeds in the future to combat UV-B stress. Data are available via ProteomeXchange with identifier PXD032163.